PRISM, a Novel Visual Metaphor Measuring Personally Salient Appraisals, Attitudes and Decision-Making: Qualitative Evidence Synthesis. - Tom Sensky; Stefan Büchi (PLoS ONE)
Background PRISM (the Pictorial Representation of Illness and Self Measure) is a novel, simple visual instrument. Its utility was initially discovered serendipitously, but has been validated as a quantitative measure of suffering. Recently, new applications for different purposes, even in non-health settings, have encouraged further exploration of how PRISM works, and how it might be applied. This review will summarise the results to date from applications of PRISM and propose a generic conceptualisation of how PRISM works which is consistent with all these applications. Methods A systematic review, in the form of a qualitative evidence synthesis, was carried out of all available published data on PRISM. Results Fifty-two publications were identified, with a total of 8254 participants. Facilitated by simple instructions, PRISM has been used with patient groups in a variety of settings and cultures. As a measure of suffering, PRISM has, with few exceptions, behaved as expected according to Eric Cassell's seminal conceptualisation of suffering. PRISM has also been used to assess beliefs about or attitudes to stressful working conditions, interpersonal relations, alcohol consumption, and suicide, amongst others. Discussion This review supports PRISM behaving as a visual metaphor of the relationship of objects (eg 'my illness') to a subject (eg 'myself') in a defined context (eg 'my life at the moment'). As a visual metaphor, it is quick to complete and yields personally salient information. PRISM is likely to have wide applications in assessing beliefs, attitudes, and decision-making, because of its properties, and because it yields both quantitative and qualitative data. In medicine, it can serve as a generic patient-reported outcome measure. It can serve as a tool for representational guidance, can be applied to developing strategies visually, and is likely to have applications in coaching, psychological assessment and therapeutic interventions.